Improving access to lymphatic filariasis MMDP services through an enhanced evidence-based, cascaded training model for health worker capacity strengthening in Ghana: an evaluation study - Ahorlu, Collins Stephen; Atinbire, Solomon Abotiba; Sedzro, Kojo Mensah; Alomatu, Bright; de Souza, Dziedzom K.; Asamenyi-Mensah, Kofi; Opare, Joseph; Saunderson, Paul; Weiland, Stefanie (Frontiers in Tropical Diseases, 2023)
Introduction Ghana has made significant progress in reducing the transmission rate of lymphatic filariasis. However, very little progress has been made in the provision of morbidity management and disability prevention (MMDP) services, which is one of the key requirements for certification of elimination as a disease of public health importance. This study was designed to compare pre-post- intervention to determine the feasibility and effectiveness of a cascade training model for health worker capacity strengthening in Ghana, using the WHO recommended minimum intervention package to improve access to MMDP services. Methods This study used a quasi-experimental design to assess the impact of evidence-based training of patients with lymphatic filariasis (LF) in the Upper West region of Ghana. All lymphedema patients who were available at the time of data collection participated in the study before and after the training. Results The mean age of respondents was 54.67 years (SD ± 16.89 years) at baseline and 54.70 years (SD ± 15.80 years) at evaluation. The majority (i.e., 76.30% at baseline and 80.50% at evaluation) of the respondents were female. Most of the respondents had not completed primary school (83.82% at baseline and 85.40% at evaluation). We found an improvement in the quality of life among LF patients, that is, the proportion of respondents who reported having a high quality of life increased from 2.9% at baseline to 20.12% at evaluation (p < 0.001). The lymphedema management practice of “hygiene/washing and drying of affected limb” was reported by 73.17% of respondents at evaluation compared with only 32.95% of respondents at baseline (p < 0.001). The acute attack management technique of “cooling the affected limb in cool water/cold compress” was reported by 70.15% of respondents at evaluation compared with 23.70% of respondents at baseline (p < 0.001). Conclusion The research confirmed that LF-related perceptions remained generally the same at baseline and evaluation among community members. The implementation of the LF-related morbidity management (MMDP) project has led to a significant improvement in the morbidity management practices among patients at evaluation compared with baseline. Our findings also showed that self-care led to an improvement in patients’ quality of life. This justifies the need for investment in morbidity management interventions in endemic communities.